Environmental services and agricultural water in South Asia: evidence from Indo-Gangetic Basin - Xenarios, Stefanos; Sharma, Bharat R.; Singh, A. (2011)
The environmental services related with agricultural water are increasingly acknowledged as a critical factor for farming development in South Asia. However, little attention is given to the demand side linked with the preservation of these services. To this aim, we conduct a stated preference approach for the elicitation of farmers? preferences towards the economic value rendered to environmental services related with agricultural water. The research is based on an extensive survey in selected clusters of India, Pakistan and Nepal. The case studies are situated along Indo-Gangetic basin due to more evidential linkages between environmental services and irrigation. The findings depict a highly agreeable stance of Indian and Nepalese farmers for the contribution to environmental services while the majority of Pakistani are opposed to such a contribution. However, they almost all agree on the type of the assessment approach while the agreeable Pakistanis offer the highest contributions. The association of the economic assessment with key wealth indicators and socio-demographic elements depicts the high significance of household size.